Post-memoria o “memoria prostética”: Virgilio Piñera a través de Teatro Avante de Miami - Rizk, Beatriz (Latin American Theatre Review, 2016)
After 35 years of ceaseless productions, the Miami group Teatro Avante in 2012 debuted Virgilio Piñera’s El no, adapted by Gilda Santana. It was their eighth staging of a work by the Cuban playwright, which started with the group’s 1978 inauguration and staging of Electra Garrigó, followed by El gordo y el flaco (1983), Falsa alarma (1986), the world premiere of Una caja de zapatos vacía (1987), Jesús (1994), El filántropo (2006), and Aire frío (2009). After reviewing the above plays, the articles concentrates on El no, which places the responsibility of dissent directly on the Cuban Revolution’s second generation. The author’s approach includes some of Alison Landsberg’s theories on the role of memory in the era of mass culture. The article also examines, from an exile perspective, Marianne Hirsch’s theories on the post-memory that second and third generations exert to recreate a past as well as their application of creative imagination in that process, especially when dealing with trauma within the family.